Mathematical Models for the Representation of Some Physiological and Quality Changes during Fruit Storage - Castellanos, Diego Alberto; Herrera, Aníbal Orlando (Journal of Postharvest Technology, 2014)
In fruits and vegetables, certain physiological processes, such as respiration  and transpiration, and quality properties, such as color, firmness or weight, are  used as consumer-based criteria of acceptability and shelf-life indicators.  Changes in the rates of oxygen consumption, carbon dioxide and water vapor  generation and product quality properties result from a series of biochemical  processes. These processes are affected by internal conditions such as the  ripening state and by external conditions such as temperature or environmental  gas concentration. Understanding the time-progress of these processes and  properties, according to variables that affect the product, and the mathematical  models that regulate them, would be beneficial in selecting the most  appropriate storage and preservation conditions to meet determined quality and  shelf-life requirements. This manuscript describes the effect of postharvest  storage conditions on biochemical and physiological processes related to  respiration and transpiration and on quality property changes. Moreover,  equations developed by many authors that describe the changes in these  processes and properties according to storage conditions are reported.
Keywords: Shelf-life Color; Postharvest storage Respiration; Transpiration